TRADITIONAL PLATEAU RESIDENCES AND TOURISTIC VALUE IN NORTHEASTERN TURKEY (ARTVIN PROVINCE) - Fatih ORHAN (Geo Journal of Tourism and Geosites, 2017)
Eastern Black Sea region, in which Artvin province is located, is one of the areas where transhumance activities are most prevalent. Besides, the activities mentioned in this region have been performed for very long years and have become traditional. One of the indispensable characteristics of transhumance activities is plateau residences with their construction techniques and architectures unique to the region. Although plateau settlements are temporary settlements that are used seasonally, plateau residences are permanent. These residences which widely reflect the cultural and socio-economical structure of the region have been constructed in a plain and natural style probably due to temporary usage. In the research field where forest cover is dense, although wood is mostly used as residence construction material, stone usage is in forefront in some regions. On the other hand there are also many residences where both materials are used together. While wooden shingle usage was widespread before as roof cover, today sheet metal usage is common. Recently the ease of transportation to plateaus and the increase in economic levels of families caused structural change in plateau residences and number of concrete structures increased gradually. This situation which was also triggered by usage for recreation purpose, constitutes a danger threatening traditional transhumance activities as well as future of rural tourism potential of plateaus. Yet the sustainability of transhumance activities which have been continuing for centuries can only be achieved by preservation of traditional structure of plateau residences.